Granulomatous enteropathy in common variable immunodeficiency: a cause of chronic diarrhoea. Issue 787 (May 1991) - Mike, N.; Hansel, T. T.; Newman, J.; Asquith, P.
Abstract : Gastrointestinal disease is a well recognized feature in patients with common variable immunodeficiency, and is often due to infection with a variety of organisms. Symptoms usually improve with appropriate antibiotic therapy and replacement gammaglobulin. We describe three middle-aged female patients with common variable immunodeficiency who had protracted diarrhoea and weight loss. Despite extensive investigation no infectious cause was found. All patients had granulomas distributed throughout the gastrointestinal tract, but no features of inflammatory bowel disease. There was a poor response to gammaglobulin replacement therapy, antibiotics or symptomatic treatment. We suggest that granulomatous enteropathy is another gastrointestinal manifestation of common variable immunodeficiency.